Anthropology of "Philosophy of Translation": Contemporary Ukrainian Philosophical Dimension - Kovtun, L. V; Shabanova, Y. O (Anthropological Measurements of Philosophical Research, 2022)
Purpose. The study is aimed at the "philosophy of translation" methodology outlining as an original philosophical texts translation tool from the point of view of culture as anthropological phenomena, namely, individuals’ participating in the text creation process providing the consistent following tasks solution: a) clarifying the text author’s role, which is the object of recipients’ perception; b) the human psyche inexhaustible potential realization for the primary text semantic content understanding by the translator to prevent its distortion; c) defining the requirements for the translation process as a mean of bringing the reader closer to author’s understanding by language barrier elimination as an intuitive "obstacle" on its way. Theoretical basis. The author proceeds from the factual absence of the "philosophy of translation" concept unambiguous definition in the modern anthropological and philosophical space and seeks to take into account all the factors affecting the newly created text quality due to the all participants’ features reviled on every stage of the text translation process. Today, the "philosophy of translation" is a widely used phrase, though ignoring the characteristics of man as a single meaning creator of the concept under study. The article provisions are based on philosophical, translation, and psychological studies with an emphasis on classical and non-classical anthropology research (Gadamer, Khoma, Holovach, Chepeleva, Dizdar, Leonov, Lotman, Bakhtin, etc.). Originality. The author proposes a methodology for the original philosophical text adaptation and presents a generalized step-by-step scheme for its translation, which helps to solve the personality of the researcher and/or translator’s influence problem on the individual author’s meaning preservation during its reproduction in a reader’s convenient language. Conclusions. A look at the "philosophy of translation" from the philosophical anthropology point of view allows us not only to consider the process of translation from the individual characteristics of all the participants (author/philosopher-reader-researcher/translator-reader-philosopher/reader) but also to describe such translation methodology by concentrating on highlighting the author’s reasoning course, which rises new knowledge and encourages further philosophical reflection within the human nature instability problem. The translation of a philosophical text not only reproduces the semantic structure of the original message but also provides a number of possible dialogical reactions to it as an object of human phenomenology. The proposed concept takes into account any reader’s needs, fully preserving the author’s position.